Redefining Modernism: Stuart Davis’s Cold War Champion series - Kamila Benayada (IdeAs)
Stuart Davis’s Champion paintings of the 1950s and ‘60s re-examine and re-conceptualize early modernism, adapting it to a new environment, by defining an esthetics of inter-relations: with his own earlier works, with French and American modernism, and with the visual environment of popular culture, thereby creating flux within a visual constellation.